Sub-terahertz transmissive reconfigurable intelligent surface for integrated beam steering and self-OOK-modulation - Dongfang Shen; Feng Lan; Luyang Wang; Tianyang Song; Munan Yang; Tianyu Hu; Yueting Li; Xiaolei Nie; Jiayao Yang; Shixiong Liang; Hongxin Zeng; Hui-Fang Zhang; et al. (Light: Science & Applications)
Abstract Boasting superior flexibility in beam manipulation and a simpler framework than traditional phased arrays, terahertz metasurface-based phased arrays show great promise for 5G-A/6G communication networks. Compared with the reflective reconfigurable intelligent surface (reflective RIS), the transmissive RIS (TRIS) offers more feasibility for transceiver multiplexing systems to meet the growing demand for high-performance beam tracking in terahertz communication and radar systems. However, the terahertz TRIS encounters greater challenges in phase shift, beam efficiency, and complex circuitry. Here, we propose a sub-terahertz TRIS based on the phase shift via Pancharatnam-Berry (PB) metasurface and self-on-off keying (OOK) modulation via Schottky diodes. The electrically reconfigurable unit cell consists of a column-wise phase resonator and a rectangular slot. An experimental retrieved equivalent lumped-element circuit model is implemented in joint field-circuit simulations and is validated by experiments. A fabricated prototype demonstrates excellent performance of TRIS with the minimum insertion loss of 2.8 dB for operational states, large bandwidth nearly covering the entire W-band for 1-bit phase shift, deep OOK amplitude modulation of 12 dB, and wide scanning range of ±60° with low specular transmission. We further implement an integrated platform combining high-speed beam steering and spatial-light modulation, verifying the point-to-point signal transmissions in different directions using the TRIS platform. The proposed TRIS with high-performance and cost-effective fabrication makes it a promising solution to terahertz minimalist communication systems, radar, and satellite communication systems.